A series of novel indazole derivatives of Sirt 1 activator as osteogenic regulators. Issue 21 (1st November 2017) - Atobe, Masakazu; Yamakawa, Natsumi; Wada, Yasuhiro; Goto, Tokuhito; Kawanishi, Masashi; Ito, Takeshi; Saito, Makoto; Takeda, Masahiro; Tabata, Takanori; Arai, Hirokazu
Graphical abstract: Abstract: A series of indazole derivatives were identified as Sirt 1 activators though high-throughput screening. Optimization of each substituent on the indazole ring led to the identification of compound13. Compound13 appeared to give the best Sirt 1 activity of the compounds tested and also showed osteogenesis activity in a cell assay. Sirt 1 activators are therefore potential candidates for the treatment of osteoporosis.